Importance of Vegetable Seed Production - Alemu, Melkam Anteneh (International Journal For Research In Agricultural And Food Science, 2019)
Vegetable production constrained by shortage of seeds/planting materials, diseases and insect pests, poor postharvest handling and poor linkage to market and market information. This paper intended to review warm season garden vegetable seed production. Ethiopia has diverse agro-ecologies for production of warm season vegetables like tomato, chili and sweet pepper as well as green beans. The high demand for horticultural products, availability of suitable agro-ecology, and increasing irrigation schemes development focusing on vegetable production, have resulted in increased demand for quality seeds of improved varieties of various vegetable crops so as to serve further boost in local production, albeit with increased investment. The increase in import of vegetable seed is attributed to expansion of irrigated vegetable production both for local consumption and export. This implies that there is a substantial demand for vegetable seeds and increase in vegetable production in Ethiopia within the reference period. The development of the vegetable sub-sector is one of the priority areas in the agricultural development strategy of Ethiopia (Ethiopian Investment Agency, 2008; 2012). Commonly grown by small scale farmers and commercial growers both during rainy and off-seasons. Since, there is no organization involved in the multiplication of vegetable seeds, access of these crop varieties is very limited. The demand is rapidly increasing. Several high yielding varieties of vegetables with improved technologies have been developed however availability of quality seed with insufficient quantities is a major constraints. In order to meet this challenge there is need to initial seeds of released varieties are multiplied and maintain annually by understand and document farmers’ preference for vegetable, variety/varieties of the preferred type(s), criteria for their preference based on their perceptions; and popularize the improved seed production packages in vegetable crops, which would in turn provide comprehensive knowledge to the seed growers regarding the recent advances in technologies.